How UML IS USED. - Dobing, Brian; Parsons, Jeffrey (Communications of the ACM, 2006)
The article focuses on the history, development and use of the Unified Modeling Language (UML). The author reviews how UML emerged in the mid-1990s through the combination of previously competing object-oriented (OO) software engineering methods. According to the author, there is little quantitative evidence on the level and nature of UML use despite widespread interest. Details related to a study examining seven UML components used in systems analysis and design are also presented. The results of the study are reviewed.